Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen pada Ruby Lash Salon Cabang Tembalang - Erlina Aprilia (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2024)
Service quality & price are important factors and roots that can provide satisfaction for its customers. So that customers feel satisfied with the service provided. The purpose of this study is to determine the effect of service quality and price on consumer satisfaction. This study uses a field research method whose sampling is done by distributing questionnaires to 100 consumers which are then analyzed using multiple linear analysis. The results of the study show that Service Quality and Price simultaneously or Together have a positive and significant effect on Consumer Satisfaction at Ruby Lash Salon, Tembalang Branch